2001
DOI: 10.1074/jbc.m008005200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cu,Zn-Superoxide Dismutase Activation by the Human Metallochaperone hCCS

Abstract: The mechanism for copper loading of the antioxidant enzyme copper, zinc superoxide dismutase (SOD1) by its partner metallochaperone protein is not well understood. Here we show the human copper chaperone for Cu,Zn-SOD1 (hCCS) activates either human or yeast enzymes in vitro by direct protein to protein transfer of the copper cofactor. Interestingly, when denatured with organic solvents, the apo-form of human SOD1 cannot be reactivated by added copper ion alone, suggesting an additional function of hCCS such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 34 publications
5
100
1
2
Order By: Relevance
“…Arabidopsis plants, the wild-type ecotype Colombia-0 and the mutant lines paa1-3 [12] and paa2-1 [13] were grown under a 16 h light/ 8 h dark cycle on soil at 23°C. For growth on agar media, seeds were surface-sterilized and sown on solid 1/2 strength Murashige and Skoog (1/2 MS) medium including 1% sucrose and 0.4% agargel [21].…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis plants, the wild-type ecotype Colombia-0 and the mutant lines paa1-3 [12] and paa2-1 [13] were grown under a 16 h light/ 8 h dark cycle on soil at 23°C. For growth on agar media, seeds were surface-sterilized and sown on solid 1/2 strength Murashige and Skoog (1/2 MS) medium including 1% sucrose and 0.4% agargel [21].…”
Section: Plant Materialsmentioning
confidence: 99%
“…In yeast, Ccs1p/Lys7p delivers copper to the Cu/ZnSOD (Sod1p) by a direct protein-protein interaction [11,12], a function which is required to maintain the activity of reactive oxygen species sensitive enzymes involved in lysine and methionine biosynthesis [13]. Since chloroplasts are a site of oxygen production it is of interest to note that O 2 and the copper chaperone for Cu/Zn superoxide dismutase (CCS) regulate posttranslational activation of Cu/ZnSOD enzymes [14] by mediating correct disulfide formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the mechanism by which SOD1 acquires Zn(II) is not fully understood, several aspects of the copper insertion by the copper chaperone for SOD1 (CCS) are well established (7)(8)(9)(10)(11)(12). More recently, Furukawa et al (13) have shown that the intrasubunit disulfide bond is correctly introduced in yeast SOD1 by the copper-bound form of yeast CCS.…”
mentioning
confidence: 99%
“…L'holo-molécule adopterait alors une conformation protégeant l'ion de cuivre jusqu'à son transfert à la SOD1. La passation du Cu de Ccs1 au site actif de la SOD1 relèverait du domaine III ; son domaine II quant à lui servirait de point d'arrimage avec la SOD1 [19]. Une particularité de la Ccs1 humaine est qu'elle peut être convertie par une simple mutation ponctuelle en une protéine ayant une activité superoxyde dismutase comparable à celle de la SOD1.…”
Section: La Distribution Intracellulaire Des Ions Cuivreunclassified